Neonatal Colonic Inflammation Increases Spinal Transmission and Cystathionine β-Synthetase Expression in Spinal Dorsal Horn of Rats with Visceral Hypersensitivity - Zhao, Liting; Xiao, Ying; Weng, Rui-Xia; Liu, Xuelian; Zhang, Ping-An; Hu, Chuang-Ying; Yu, Shan P.; Xu, Guang-Yin (Frontiers in Pharmacology, 2017)
Irritable bowel syndrome (IBS) is a common gastrointestinal disorder characterized by chronic abdominal pain and alteration of bowel movements. The pathogenesis of visceral hypersensitivity in IBS patients remains largely unknown. Hydrogen sulfide (H2S) is reported to play an important role in development of visceral hyperalgesia. However, the role of H2S at spinal dorsal horn level remains elusive in visceral hypersensitivity. The aim of this study is designed to investigate how H2S takes part in visceral hypersensitivity of adult rats with neonatal colonic inflammation (NCI). Visceral hypersensitivity was induced by neonatal colonic injection of diluted acetic acid. Expression of an endogenous H2S synthesizing enzyme cystathionine β-synthetase (CBS) was determined by Western blot. Excitability and synaptic transmission of neurons in the substantia gelatinosa (SG) of spinal cord was recorded by patch clamping. Here we showed that expression of CBS in the spinal dorsal horn was significantly upregulated in NCI rats. The frequency of glutamatergic synaptic activities in SG was markedly enhanced in NCI rats when compared with control rats. Application of NaHS increased the frequency of both spontaneous and miniature excitatory postsynaptic currents of SG neurons in control rats through a presynaptic mechanism. In contrast, application of AOAA, an inhibitor of CBS, dramatically suppressed the frequency of glutamatergic synaptic activities of SG neurons of NCI rats. Importantly, intrathecal injection of AOAA remarkably attenuated visceral hypersensitivity of NCI rats. These results suggest that H2S modulates pain signaling likely through a presynaptic mechanism in SG of spinal dorsal horn, thus providing a potential therapeutic strategy for treatment for chronic visceral pain in patients with IBS.